Strategi Jual Beli Kue Ulang Tahun dengan Sistem Pesanan Menurut Perspektif Ekonomi Islam (Studi Kasus di Aroma Bakery and Cakeshop Sibuhuan) - Amhar Maulana Harahap,; Nur Jannah Nasution,; Yeni Warida Lubis, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims: (1) To find out the strategy for buying and selling orders in Islamic economics. (2) To find out the strategy for buying and selling birthday cakes using an order system according to an Islamic economic perspective at Aroma Bakery and Cakeshop Sibuhuan. The results of the research show that: (1) The Order Buying and Selling Strategy in Islamic Economics must fulfill the pillars of order buying and selling, namely the parties involved (seller and buyer), the object of the transaction for the goods being contracted, the order price or capital paid and the qobul agreement. For the terms of sale and purchase orders, the money must be paid in part and the remainder after completion of the order, the goods become a debt for the seller, the goods can be delivered according to the time promised, the size of the goods must be clear, the nature of the goods known and stated, and the place of recipient stated. Apart from being harmonious and the conditions being met, it is clear that the product is appropriate and everything meets the rules. Meanwhile, if the buyer feels that the goods they ordered do not comply with the specifications, the seller will be fully responsible if the negligence was indeed from the seller himself (2) Strategy for Buying and Selling Birthday Cakes Using an Order System According to an Islamic Economic Perspective at Aroma Bakery and Cakeshop Sibuhuan has been completed. according to where the terms and conditions for buying and selling orders have been fulfilled, namely ordering the desired product either via the Facebook, Instagran or Whatsapp application, or you can go directly to Aroma Bakery and Cakeshop Sibuhuan, if the order has been confirmed and approved by both parties then the buyer will be directed to make payment of receipts via transfer according to the account number provided by the admin for those who order the Facebook, Instagran or Whatsaap application, and pay directly for orders who go directly to Aroma Bakery and Cakeshop Sibuhuan. If the payment transaction has been completed by the buyer, the buyer sends proof of transfer to the admin, then after the buyer's order is processed, it will be sent according to the schedule set by both parties.